(untitled) (American Journal of Youth and Women Empowerment, 2022)
Parenting differs from child rearing. In the child rearing emphasis is on the act of training or bringing up the children and the interaction between the parents and child, while parenting emphasizes the responsibilities and qualities of exemplary behavior of the parent. The study utilized a descriptive method with the questionnaire as the instrument of the study. It was found out in the study that the profile of parents of Grades 5 and 6 students in Calbayog III District are composed of both parents, middle age, finished if not completed elementary level of education has more number members in the family, average earner and has no active community affiliations. The parenting style of parents is authoritative. This implies that the Grade 5 and 6 parents in Calbayog District III are nurturing, responsive, and supportive, yet set firm limits for their children. They attempt to control children’s behavior by explaining rules, discussing, and reasoning. They listen to a child’s viewpoint but don’t always accept it.